Correlates of protection against Neisseria Meningitidis. - Pollard, A (Nature Publishing Group, 2016)
Over the past two decades, the leading cause of meningitis in childhood and the leading infectious cause of death in the UK has been Neisseria meningitidis. There is now the potential for broad control of this serious disease by vaccination.